Thyroxine Induces Acute Relaxation of Rat Skeletal Muscle Arteries via Integrin αvβ3, ERK1/2 and Integrin-Linked Kinase - Selivanova, Ekaterina K.; Gaynullina, Dina K.; Tarasova, Olga S. (Frontiers in Physiology, 2021)
Aim. Hyperthyroidism is associated with a decreased peripheral vascular resistance, which could be caused by the vasodilator genomic or nongenomic effects of thyroid hormones. Nongenomic, or acute, effects develop within several minutes and involve a wide tissue-specific spectrum of molecular pathways poorly studied in vasculature. We aimed to investigate the mechanisms of acute effects of thyroid hormones on rat skeletal muscle arteries. Methods. Sural arteries from male Wistar rats were used for isometric force recording (wire myography) and phosphorylated protein content measurement (Western blotting). Results. Both T3 and T4 reduced contractile response of sural arteries to α1-adrenoceptor agonist methoxamine. The effect of T4 was more prominent than T3 and not affected by iopanoic acid, an inhibitor of deiodinase 2. Endothelium denudation abolished the effect of T3, but not T4. Integrin αvβ3 inhibitor tetrac abolished the effect of T4 in endothelium-denuded arteries. T4 weakened methoxamine-induced elevation of phospho-MLC2 (Ser19) content in arterial samples. The effect of T4 in endothelium-denuded arteries was abolished by ERK1/2 inhibitor U0126 as well as ILK inhibitor Cpd22 but persisted in the presence of Src- or Rho-kinase inhibitors (PP2 and Y27632, respectively). Conclusion. Acute nongenomic relaxation of sural arteries induced by T3 is endothelium-dependent and that induced by T4 is endothelium-independent. The effect of T4 on α1-adrenergic contraction is stronger compared to T3 and involves the suppression of extracellular matrix signaling via integrin αvβ3, ERK1/2 and ILK with subsequent decrease of MLC2(Ser19) phosphorylation.